Of Love, Loss and Love Lost: The (uncompleted) Reception of Rabindranath Tagore in Spain (Politeja, 2016)
The paper is a concise review of the reception of Rabindranath Tagore in Spain and the crucial role played by the Spanish writer Juan Ramón Jiménez and his wife Zenobia Camprubí in promoting the poetry of the “great Bard of Bengal,” not only in Spain but in the whole Spanish‑speaking world, with their marvelous translations produced mostly between 1913 and 1922. The piece describes how biographical factors (the couple’s own love story), literary contexts (the search for a new lyrical voice in Spanish poetry after modernism) and the progressive intellectual and political milieu of the first decades of the twentieth century converged in the unique response Tagore received in Spain, though he never visited the country. It also analyses why the admiration for Tagore persisted for decades even after the changes brought by Franco’s regime.